Handbook of industrial hydrocarbon processes - Speight, James G. (Gulf Professional, 2009)
Written by an author with over 38 years of experience in the chemical and petrochemical process industry, this handbook will present an analysis of the process steps used to produce industrial hydrocarbons from various raw materials. It is the first book to offer a thorough analysis of external factors effecting production such as: cost, availability and environmental legislation. An A-Z list of raw materials and their properties are presented along with a commentary regarding their cost and availability. Specific processing operations described in the book include: distillation, thermal cracking and coking, catalytic methods, hydroprocesses, thermal and catalytic reforming, isomerization, alkylation processes, polymerization processes, solvent processes, water removal, fractionation and acid gas removal. o Flow diagrams and descriptions of more than 250 leading-edge process technologies. o An analysis of chemical reactions and process steps that are required to produce chemicals from various raw materials o Properties, availability and environmental impact of various raw materials used in hydrocarbon processing